2008
DOI: 10.1159/000172617
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Second Screening Point for Detection of Coronary Artery Disease in Hemodialysis Patients without Advanced Coronary Artery Disease

Abstract: Background: Screening for coronary artery disease (CAD) at the initiation of dialysis is a K/DOQI recommendation. However, it remains unclear when screening for CAD should be repeated in patients without significant disease at the time of starting dialysis. The objectives of this study were to determine: (1) the survival of hemodialysis (HD) patients without CAD at the initiation of dialysis, (2) the major predictors of CAD events, and (3) the best time to repeat screening for CAD after the initiation of HD. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…56 Of 100 hemodialysis patients with a normal coronary angiography and/or MPS, 5 developed a major adverse cardiac event during the second year following the test. 80 A normal MPS (normal global perfusion and left ventricular ejection fraction 445%) was associated with a 2-year cardiac event rate of 15%. 23 These data should be compared with cardiac event rates below 1% per year following a normal MPS in the general population.…”
Section: Who Deserves To Be Screened?mentioning
confidence: 97%
“…56 Of 100 hemodialysis patients with a normal coronary angiography and/or MPS, 5 developed a major adverse cardiac event during the second year following the test. 80 A normal MPS (normal global perfusion and left ventricular ejection fraction 445%) was associated with a 2-year cardiac event rate of 15%. 23 These data should be compared with cardiac event rates below 1% per year following a normal MPS in the general population.…”
Section: Who Deserves To Be Screened?mentioning
confidence: 97%
“…The second possible explanation may relate to the results of our previous study [26]. In that study, we analyzed the survival rates for major adverse cardiac events in incident dialysis patients without CAD and found that even in patients without significant CAD, cardiac events occurred after 1 year of starting dialysis.…”
Section: Effect Of Cad Screening On Mortalitymentioning
confidence: 88%
“…They showed that no cardiovascular events were observed during the first year of HD in 100 patients without CAD at the initiation of dialysis and five events occurred during the second year of dialysis. They proposed that the optimum time to repeat screening for CAD might be at the end of the first year of dialysis . Our findings were consistent with their results.…”
Section: Discussionmentioning
confidence: 99%